Money Supply and Economic Growth in Nepal: Empirical Evidence from 1975–2022 - Basnet, Bhawana; Gyanwaly, Ram Prasad (Economic Journal of Nepal, 2024)
This study investigates the relationship between money supply and economic growth in Nepal from 1975 to 2022. While monetary policy is widely recognized as an important policy lever for economic development, the specific mechanisms by which the money supply influences growth remain poorly understood in Nepal's context, particularly regarding how different monetary aggregates affect real economic activity and the behavioral constraints on monetary policy. This study examines the long- and short-run relationships between various measures of the money supply and economic growth using secondary time-series data from the Nepal Rastra Bank and the Central Bureau of Statistics. The analysis employs accounting and money multiplier approaches to examine money creation process, supplemented by econometric techniques such as unit root tests, cointegration analysis, vector error correction models. The study reveals significant positive long-run relationships between real money supply and real GDP growth, with elasticities of 0.28 for narrow money (M1) and 0.27 for broad money (M2). Broad money adjusts more rapidly to equilibrium than narrow money, indicating differential speeds of adjustment in Nepal's monetary system. However, the money multiplier analysis shows that behavioral factors, such as currency leakage and financial intermediation patterns, substantially constrain the central bank's ability to control the money supply precisely with conventional policy tools. These findings indicate that monetary policy can meaningfully influence economic growth in Nepal. However, its effectiveness depends on understanding the specific transmission channels and addressing broader financial development issues, particularly financial inclusion and reducing currency leakage from the banking system.